DETERMINAN PENINGKATAN KINERJA PEGAWAI: ANALISIS PENGARUH GAYA KEPEMIMPINAN, PELATIHAN, DAN MOTIVASI EKSTRINSIK - Diyas Timor Purnawan; Yohanes Joni Pambelum; Meirani Harsasi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze the effect of situational leadership style and training on employee performance and the influence of extrinsic motivation as a mediating variable. The sample used in this study was 75 employees of the National Narcotics Agency within the West Nusa Tenggara Province. The data collection technique used is to use a questionnaire that has been tested for validity and reliability, further tested using path analysis. The results of the hypothesis test with the SmartPLS 3.0 application showed several findings, including: Situational leadership style has a positive and significant effect on employee performance, Training has a positive but not significant effect on employee performance, Extrinsic motivation has a positive and significant effect on employee performance, Situational leadership styles have a positive and significant effect on extrinsic motivation. Training has a positive and significant effect on extrinsic motivation. Situational leadership style through extrinsic motivation has a positive and significant effect on employee performance, and Training through extrinsic motivation has a positive and significant effect on employee performance